ISLAMIC EDUCATION MANAGEMENT FACING INDUSTRY 4.0 AND SOCIETY 5.0: INNOVATIVE LEADERSHIP TRANSFORMATION STRATEGIES BASED ON ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY, WEB PLATFORMS, AND VIRTUAL REALITY TO OPTIMISE INSTITUTIONAL PERFORMANCE BASED ON A REVIEW OF THE LATEST LITERATURE - Abdul Rahman; Aslan Aslan (Indonesian Journal of Education (INJOE), 2025)
This study examines the transformation of Islamic education management in facing the challenges of Industry 4.0 and Society 5.0 through innovative leadership strategies based on artificial intelligence (AI) technology, web platforms, and virtual reality (VR). Using a literature review approach, the results show that the synergy of these technologies optimises the performance of Islamic educational institutions, despite the challenges of infrastructure and digital ethics. This study concludes that transformational leadership based on maqasid sharia is the key to creating a holistic educational ecosystem that is efficient, inclusive, and relevant to the digital era. Recommendations include digital literacy training for leaders, productive waqf funding for infrastructure, and further empirical research to validate the model. This study contributes to the development of contemporary Islamic education management theory that combines spirituality with technological innovation for the benefit of the community.